A Novel Family with Demyelinating Charcot-Marie-Tooth Disease Caused by a Mutation in the PMP2 Gene: A Case Series of Nine Patients and a Brief Review of the Literature - Margherita Baga; Susanna Rizzi; Carlotta Spagnoli; Daniele Frattini; Francesco Pisani; Carlo Fusco (MDPI AG, 2023)
Introduction: Charcot-Marie-Tooth (CMT) is a group of inherited peripheral neuropathies characterized by wide genotypic and phenotypic variability. The onset is typically in childhood, and the most frequent clinical manifestations are predominantly distal muscle weakness, hypoesthesia, foot deformity (pes cavus) and areflexia. In the long term, complications such as muscle-tendon retractions, extremity deformities, muscle atrophy and pain may occur. Among CMT1, demyelinating and autosomal dominant forms, CMT1G is determined by mutations in the PMP2 myelin protein. Results: Starting from the index case, we performed a clinical, electrophysiological, neuroradiological and genetic evaluation of all family members for three generations; we identified p.Ile50del in PMP2 in all the nine affected members. They presented a typical clinical phenotype, with childhood-onset variable severity between generations and a chronic demyelinating sensory-motor polyneuropathy on the electrophysiologic examination; the progression was slow to very slow and predominant in the lower limbs. Our study reports a relatively large sample of patients, members of the same family, with CMT1G by PMP2, which is a rare form of demyelinating CMT, highlighting the genetic variability of the CMT family instead of the overlapping clinical phenotypes within demyelinating forms. To date, only supportive and preventive measures for the most severe complications are available; therefore, we believe that early diagnosis (clinical, electrophysiological and genetic) allows access to specialist follow-up and therapies, thereby improving the quality of life of patients.